PENGEMBANGAN MEDIA PEMBELAJARAN FISIKA BERBASIS ANDROID UNTUK SISWA SMA KELAS XII MENGGUNAKAN APLIKASI APP INVENTOR 2 - Januarti, Januarti; M. Rahmad, M. Rahmad; M. Syafi'i, M. Syafi'i (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to produce an physics learning media based on android static electricity material, as well as knowing the quality of learning media products that have been developed so that they are suitable for use in physics learning activities. This learning media is designed to contain static electricity material that is abstract and cannot be seen in plain view. In this learning media the material of the picture is real and easily understood by students. This research is a research and development (R & D) which refers to the ADDIE model which consists of five stages, namely: analyze, design, development, implementation and evaluation stages. The learning media produced is an andoid based mobile learning application using APP Inventor 2. The assessment instrument uses an assessment sheet with data sources from media experts and metrics experts. This assessment instrument consists of four aspects of assessment, one of which is the design aspect, pedagogical aspects, content aspects and technical aspects. The results of the assessment of these four aspects obtained an average score of 4.66 and r index of 0.91 with a high level of validity. The results of the assessment indicate that the results of data analysis indicate that the static-based android learning media for high school students of class XII runs well and can be used as a supporting medium in the learning process at school.Key Words: Physics Learning Media, Inventor App For Android, Static Electricity.